The role of individual variation in marine larval dispersal - Nanninga, Gerrit B.; Berumen, Michael L. (Frontiers in Marine Science, 2014)
The exchange of individuals among patchy habitats plays a central role in spatial ecology and metapopulation dynamics. Dispersal (e.g. short vs. long) is frequently observed to vary non-randomly within populations, indicating that variability among individuals may shape heterogeneity in patterns of connectivity. The concept of context- and condition-dependent dispersal describes the balance between the costs and benefits of dispersal that arises from the interaction of temporal and spatial landscape heterogeneity (the context) with phenotypic variability among individuals (the condition). While this hypothesis is widely accepted terrestrial theory, it remains questionable to what extent the concept of adaptive dispersal strategies may apply to marine larval dispersal, a process that is largely determined by stochastic forces. Yet, larvae of many taxa exhibit strong navigational capabilities and there is mounting evidence of widespread intra-specific variability in biological traits that are potentially correlated with dispersal potential. While so far there are few known examples of real larval dispersal polymorphisms, intra-specifically variable dispersal strategies may be common in marine systems. Whether adaptive or not, it is becoming apparent that inter-individual heterogeneity in morphology, behaviour, condition, and life history traits may have critical effects on population-level heterogeneity in dispersal. Here, we explore the eco-evolutionary causes and consequences of intrinsic and extrinsic variability on larval dispersal by synthesizing the existing literature and drawing conceptual parallels from terrestrial theory. We emphasize the potential importance of larval dispersal polymorphisms in marine population dynamics.